Digital moviemaking - Gross, Lynne S. (Wadsworth Cengage Learning, 2009)
Digital Moviemaking, a concept in its infancy when this book was first published in 1991, has become the norm. The use of electronic equipment in conjunction with traditional film techniques is now widepread, both academically and professionally. However, technology and techniques continue to evolve, so this edition has many revisions